Posterior Condylar Foramen: A Study on Dried Adult Pakistani Skulls - BRISHNA KHAN, ALIYA ZAHID, MUHAMMAD WAJAHAT KHAN (Journal of Fatima Jinnah Medical University, 2018)
Posterior condylar foramen is among the largest emissary foramina of the human skull. It opens in the floor of a condylar fossa situated behind the occipital condyles of occipital bone on base of skull on either side of foramen magnum Type of study: Descriptive cross sectional study Objectives: To study the incidence and morphology of posterior condylar foramen in dried skulls of cadavers of Pakistani population. Materials and Method: This study was carried out in Anatomy departments of Khawaja Muhammad Safdar Medical College Sialkot and Allama Iqbal Medical College Lahore. For this purpose, 78 adult skulls (156 sides) were included irrespective of age and sex. They were closely observed for presence of posterior condylar foramina. Their patency was checked by a probe and their intracranial openings were also noted Results: It was observed that out of 78 skulls, 26(33.3%) showed unilateral posterior condylar foramen (9 on left side and 17 on right side), 48 (61.6%) skulls had bilateral posterior condylar foramina and 4 (5.1% ) skulls had no posterior condylar foramen. Out of 9 left sided posterior condylar foramina, 4 are patent and rest are not patent. On right side, 13 are patent and only 4 are blind. It was also observed that out of total 72 patent posterior condylar foramina ,44 (61%) ( had openings in sigmoid sinus sulcus in posterior cranial fossa (intrasinus type) and 28 (39%) had retrosinus openings ( posterior to sigmoid sinus sulcus). Conclusion: Knowledge of anatomical variations of the posterior condylar foramina are clinically important as they are one of the significant anatomical landmarks for surgical approaches through foramen magnum and during surgical resection of tumours or other space occupying lesions from the cranial base. Since no such data about posterior condylar foramina is available in Pakistani population, this study may be of crucial importance to neurosurgeons, radiologists and anatomists.